2024
DOI: 10.1088/2632-959x/ad2b83
|View full text |Cite
|
Sign up to set email alerts
|

An empirical experimental observations and MD simulation data-based model for the material properties of confined fluids in nano/Angstrom size tubes

Ashish Garg,
Swati Bishnoi

Abstract: The transport of fluids in nano/Angstrom-sized pores has gotten much attention because of its potential uses in nanotechnology, energy storage, and healthcare sectors. Understanding the distinct material properties of fluids in such close confinement is critical and dictate the fluid's behavior in determining flow dynamics, transport processes, and, ultimately, the performance of nanoscale devices. Remarkably, many researchers observed that the size of the geometry, such as confining nanotube diameter, exerts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Consequently, characterizing these critical properties: density ρ, viscosity η, and slip length λ require a consolidated modelling effort as a function of dimensions of the nanogeometries. While Garg and Bishnoi [14] proposed a generic and user-friendly model for predicting fluid properties within nanotubes, a comparable unified modeling approach remains elusive for understanding how these properties change in nanochannels. Our review of the literature revealed an interesting discrepancy.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, characterizing these critical properties: density ρ, viscosity η, and slip length λ require a consolidated modelling effort as a function of dimensions of the nanogeometries. While Garg and Bishnoi [14] proposed a generic and user-friendly model for predicting fluid properties within nanotubes, a comparable unified modeling approach remains elusive for understanding how these properties change in nanochannels. Our review of the literature revealed an interesting discrepancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, when subsequent daughter channel dimensions shrink to the nanoscale, additional complexities emerge. Particularly, the characteristics of Newtonian fluids start to rely on the geometric attributes of the network [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, as subsequent daughter channel dimensions shrink to the nanoscale, additional complexities arise. Notably, the very properties of Newtonian fluids begin to depend on the network's geometric features [15][16][17].…”
Section: Introductionmentioning
confidence: 99%